Proceedings of the ACM Symposium on Principles of Distributed Computing 2017
DOI: 10.1145/3087801.3087826
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized Segregation on the Grid

Abstract: We consider an agent-based model with exponentially distributed waiting times in which two types of agents interact locally over a graph, and based on this interaction and on the value of a common intolerance threshold τ , decide whether to change their types. This is equivalent to a zero-temperature Ising model with Glauber dynamics, an Asynchronous Cellular Automaton (ACA) with extended Moore neighborhoods, or a Schelling model of self-organized segregation in an open system, and has applications in the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…By a region of expansion we mean a region of expansion of only one type (θ). The next lemma, which is a restatement of Lemma 8 in [22], shows that as long as τ ∈ (τ * , 1/2), w.h.p. a monochromatic block on G w can make an exponentially large area monochromatic.…”
Section: Lemma 2 ([24]mentioning
confidence: 81%
See 1 more Smart Citation
“…By a region of expansion we mean a region of expansion of only one type (θ). The next lemma, which is a restatement of Lemma 8 in [22], shows that as long as τ ∈ (τ * , 1/2), w.h.p. a monochromatic block on G w can make an exponentially large area monochromatic.…”
Section: Lemma 2 ([24]mentioning
confidence: 81%
“…In the two-dimensional model case, Immorlica et al [21] have shown for the Glauber dynamics that for τ ∈ (1/2 − , 1/2) the expected size of the monochromatic region is exponential in the size of the neighborhood. This -size interval has been enlarged in a previous work by the authors [22] to 0.433 < τ < 1/2 (and by symmetry 1/2 < τ < 0.567). In the same work, the interval has been further extended to 0.344 < τ ≤ 0.433 (and by symmetry for 0.567 ≤ τ < 0.656) considering "almost monochromatic" regions, namely regions where the ratio of the number of particles in one state and the number of particles in the other state quickly vanishes as the size of the neighborhood grows.…”
Section: Introductionmentioning
confidence: 92%
“…Close to our model is the work by Omidvar and Franceschetti [34,35], who initiated an analysis of the size of monochrome regions in the so called Schelling Spin Systems. Agents of two different types are placed on a grid [34] and a geometric graph [35], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Close to our model is the work by Omidvar and Franceschetti [34,35], who initiated an analysis of the size of monochrome regions in the so called Schelling Spin Systems. Agents of two different types are placed on a grid [34] and a geometric graph [35], respectively. Then independent and identical Poisson clocks are assigned to all agents and, every time a clock rings, the state of the corresponding agent is flipped if and only if the agent is discontent w.r.t.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation